2014
DOI: 10.1155/2014/926481
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemic PRP in Tendon Cells

Abstract: Platelet-rich plasma (PRP) is injected within tendons to stimulate healing. Metabolic alterations such as the metabolic syndrome, diabetes, or hyperuricemia could hinder the therapeutic effect of PRP. We hypothesise that tendon cells sense high levels of uric acid and this could modify their response to PRP. Tendon cells were treated with allogeneic PRPs for 96 hours. Hyperuricemic PRP did not hinder the proliferative actions of PRP. The gene expression pattern of inflammatory molecules in response to PRP show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…A possible source of increased serum MCP-1 includes not only circulating monocytes and macrophages but also local cells such as tenocytes. Notwithstanding in our cell culture model, hyperuricemia is a minor stressor for tenocytes that does not induce changes in MCP-1 but in the synthesis of IL-8 confirming a previous study 6 . However, we cannot rule out that hyperuricemia could modify the polarization of infiltrating monocytes/macrophages 18 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A possible source of increased serum MCP-1 includes not only circulating monocytes and macrophages but also local cells such as tenocytes. Notwithstanding in our cell culture model, hyperuricemia is a minor stressor for tenocytes that does not induce changes in MCP-1 but in the synthesis of IL-8 confirming a previous study 6 . However, we cannot rule out that hyperuricemia could modify the polarization of infiltrating monocytes/macrophages 18 .…”
Section: Discussionsupporting
confidence: 90%
“…However, hyperuricemia is a nondramatic alteration of tissue homeostasis, in contrast to the more substantial alteration provoked when uric acid condensates, and forms monosodium urate (MSU) crystals, the hallmark of gout. Recently, we have shown that high concentrations of uric acid in the tendon cell microenvironment involve a mild alteration in extracellular matrix homeostasis in the context of platelet rich plasma (PRP) 6 . PRP is a plasma preparation, obtained from autologous peripheral blood that contains a platelet level above peripheral blood and, as often found in tendon treatment, it can hold a high concentration of leukocytes (L-PRP) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Samples were obtained after receiving informed consent from patients and local ethics committee approval. Tendon cells were isolated by an explant procedure and cultured as previously described [9]. All the experiments were performed in cells at passages between two and three, ie, to avoid dedifferentiation no more than three times the cells in the culture have been split and subcultured.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PRP releases a known chemotactic cytokine for neutrophils, CXCL8/IL8. Moreover, we have recently shown that these chemotactic signals are reinforced and augmented by local cell synthesis in vitro [13]. PRP can also modify the lifespan of infiltrated leukocytes by modifying the molecular environment of the injury.…”
Section: Polimorphonuclear Cell (Pmns) Infiltrationmentioning
confidence: 97%